2012
DOI: 10.1021/nl2043503
|View full text |Cite
|
Sign up to set email alerts
|

Superheating Water by CW Excitation of Gold Nanodots

Abstract: A temperature-dependent photoluminescent thin film of Al(0.94)Ga(0.06)N doped with Er(3+) is used to measure the temperature of lithographically prepared gold nanodots. The gold nanodots and thin film are excited simultaneously with a continuous wave (CW) Nd:YAG 532 nm laser. The gold nanodot is submersed under water, and the dot is subsequently heated. The water immediately surrounding the nanodot is superheated beyond the boiling point up to the spinodal decomposition temperature at 594 ± 17 K. The spinodal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
143
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(147 citation statements)
references
References 21 publications
3
143
0
1
Order By: Relevance
“…Examples include the melting point depletion in molecular clusters, [15][16][17] capillary condensation and evaporation in nanoporous materials, 18,19 and delay of crystallization in small confinements 20,21 or of vaporization around nanoparticles. 22 Here we show that it is not only possible to delay these phase transitions, but to go one step further and completely impede nucleation in small closed systems. We shall see that this superstabilization of fluids takes place when the new phase becomes unavailable, typically due to limitations in volume and number of particles.…”
mentioning
confidence: 77%
“…Examples include the melting point depletion in molecular clusters, [15][16][17] capillary condensation and evaporation in nanoporous materials, 18,19 and delay of crystallization in small confinements 20,21 or of vaporization around nanoparticles. 22 Here we show that it is not only possible to delay these phase transitions, but to go one step further and completely impede nucleation in small closed systems. We shall see that this superstabilization of fluids takes place when the new phase becomes unavailable, typically due to limitations in volume and number of particles.…”
mentioning
confidence: 77%
“…For a long time, the bubble emergence under the pulsed laser illumination was the main object of interest [6,[14][15][16][17]. Large amount of energy supplied by the short laser pulse results in very rapid water evaporation and bubble growth followed by the high-speed collapse with possible rebounds and energy release in form of luminescence and/or shock waves (optical cavitation).…”
Section: Introductionmentioning
confidence: 99%
“…As far as the steam generation mechanism is concerned, it has been shown analytically that a minimum radiation flux of 3×10 8 W/m 2 is required to produce nanobubbles on heated nanoparticles [46,49,50], which can only be reached by powerful laser beams. In a separated study, Julien et al [51] showed that 1×10 10 W/m 2 was required to generate a nanobubble on a plasmonic gold nanoparticle.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the volumetric heating, direct vapor generation due to localized heating of the As far as the steam generation mechanism is concerned, for nanobubbles to be produced around heated nanoparticles, it has been shown analytically that a minimum radiation flux of 3×10 8 W/m 2 is required to produce nanobubbles on heated nanoparticles [46,49,50], which can may only be reached developed by powerful laser beams. In a separated theoretical study, of the nanobubble development kinetics around plasmonic gold nanoparticle by Julien et al [51] showed that to generate a nanobubble, a flux intensity of around 1×10 10 W/m 2 was required to 5 generate a nanobubble on a plasmonic gold nanoparticle.…”
Section: Introductionmentioning
confidence: 99%